2015
DOI: 10.1002/adma.201500218
|View full text |Cite
|
Sign up to set email alerts
|

Localized Neuron Stimulation with Organic Electrochemical Transistors on Delaminating Depth Probes

Abstract: Organic electrochemical transistors are integrated on depth probes to achieve localized electrical stimulation of neurons. The probes feature a mechanical delamination process which leaves only a 4 μm thick film with embedded transistors inside the brain. This considerably reduces probe invasiveness and correspondingly improves future brain-machine interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
176
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(178 citation statements)
references
References 22 publications
1
176
0
1
Order By: Relevance
“…Gas sensing with PEDOT:PSS OECTs was performed by adjusting the polymer thickness resulting in a response to nitric oxide with a limit of detection of 350 ppb (Lin et al 2009). Similar devices were also used for in vitro cell action potential measurements (Cellot et al 2015), and for in vivo applications (Khodagholy et al 2011;Ludwig et al 2006;Williamson et al 2015). The gating mechanism of the OECTs to record electrophysiological signals differs drastically from that of the classical silicon fieldeffect transistors (FET) where capacitive coupling of signal components and purely potentiometric sensing is done to record the ionic currents occurring in cell action potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Gas sensing with PEDOT:PSS OECTs was performed by adjusting the polymer thickness resulting in a response to nitric oxide with a limit of detection of 350 ppb (Lin et al 2009). Similar devices were also used for in vitro cell action potential measurements (Cellot et al 2015), and for in vivo applications (Khodagholy et al 2011;Ludwig et al 2006;Williamson et al 2015). The gating mechanism of the OECTs to record electrophysiological signals differs drastically from that of the classical silicon fieldeffect transistors (FET) where capacitive coupling of signal components and purely potentiometric sensing is done to record the ionic currents occurring in cell action potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, organic electrochemical transistors are a type of electrolyte-gated transistors in which the constituting semiconducting ionomer blend has a good affinity with cations. As such, this platform is extensively studied as a bio-electronical interface to measure neural activity [7,8,9]. Nowadays, one of the key challenges for this technological tool is to interpret complex readouts of dense networks.…”
Section: Introductionmentioning
confidence: 99%
“…The same research group realized the architecture reported in [129] over a rigid and removable shuttle, hence fabricating a penetrating and flexible neural interface, where an OECT and an adjacent surface electrode can be inserted deep into the brain [130]. The surface electrode could be used as a local gate for each transistor, as a sink for stimulation currents, or as a simple recording and/or stimulating electrode.…”
Section: Organic Field-effect Transistorsmentioning
confidence: 99%